Ancient astrology - Barton, Tamsyn, 1962- (Sciences of antiquity., 1994)
An account of astrology from its beginnings in Mesopotamia, focusing on the Greco-Roman world, Ancient Astrology examines the theoretical development and changing social and political role of astrology.